Exploring the Integration of ChatGPT in Catholic Religious Education and Character Development: Students’ Experience and Use Patterns - Saraswati, Chris Cerly Rika; Wahyono, Sugeng Bayu (Jurnal Paedagogy, 2026)
This study aims to explore the integration of ChatGPT in Catholic Religious Education and Character Development, focusing on students’ learning experiences, usage patterns, levels of awareness, and reasons for adopting the tool as a learning support. A qualitative phenomenological approach was employed to capture students’ lived experiences in using generative artificial intelligence in learning activities. The participants consisted of six junior high school students from Grades VII, VIII, and IX who were purposively selected based on their experience using ChatGPT in academic contexts. Data were collected through in-depth interviews, classroom observations, documentation, supplementary questionnaires, and field notes. Data credibility was ensured through method and source triangulation, as well as member checking. The data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing and verification. The findings indicate that students use ChatGPT to deepen their understanding of learning materials and to support the completion of academic tasks. Two main patterns of use emerged, namely reflective and pragmatic, which shape how students engage with the technology. The integration of ChatGPT appears to contribute more strongly to the development of integrity-related values than relational values, underscoring the importance of sustained pedagogical guidance from teachers. These findings suggest that the purposeful integration of generative artificial intelligence, supported by reflective educational guidance, can promote both academic understanding and character formation. This approach also offers a transferable framework for the responsible integration of AI in faith-based educational institutions.